En defensa al derecho de las clases excluidas: Una propuesta en base al pensamiento y obra de Miguelina Acosta Cárdenas - Huamaní Rimachi, Erika Márjory (2021)
There is no greater value for “the other” than human dignity, an inalienable right that seeks equality and revalues all excluded classes. This paper aims to collect the philosophical thought of Miguelina Acosta through a systematic study of her life and work, approached from a contemporary perspective focused on neoindigenism. To this end, we will first analyze the dissonance between the factual reality and the Peruvian legal structure that disfavor the causes of neoindigenist struggle, in particular, those that affect their livelihood with an effect on their natural resources. Secondly, we will analyze the implications of the visibility of the social claim as a driving force for change, which is also necessary in a class-based society that ignores “the other”. Finally, the need for social awareness will be evaluated as a preponderant factor for the sustainability of change. From the constructive analysis, the need to develop a solution perspective that encompasses the three perspectives studied, not as a cause-effect sequence of one over the other, but as a mutual coexistence that guarantees the success of the others, can be raised. Therefore, in order to be able to find an effective proposal to the excluded classes, we conclude that there is a need for a trisustainable development model based on the aforementioned Premises.